The Overall Plant-based Diet Index During Pregnancy and Risk of Gestational Diabetes Mellitus: A Prospective Cohort Study. (29th May 2020) - Wang, Huanzhuo; Huang, Li; Zhong, Chunrong; Chen, Renjuan; Zhou, Xuezhen; Zhang, Yu; Chen, Xi; Li, Qian; Li, Nan; Lin, Lixia; Gao, Duan; Hao, Liping; et al.
Abstract: Objectives: The overall plant-based diet index (PDI) has been demonstrated to be protective against type 2 diabetes (T2D) in the general population. Whether the PDI was linked to gestational diabetes mellitus (GDM) is unclear. We aimed to assess the association of the PDI with GDM incidence in Chinese pregnant women. Methods: A total of 2099 pregnant women from the Tongji Maternal and Child Health Cohort (TMCHC) were included in the present study. Dietary data were collected at 13–28 wks of pregnancy by using a validated semi-quantitative food frequency questionnaire (FFQ). Food groups including cereals, fruits, vegetables, nuts, beans, vegetable oil, dairy, eggs, meat, and fish, were ranked into quintiles and given positive (1–5 for plant food groups) or reverse (5–1 for animal food groups) scores. The PDI was obtained by summing the 10 food group scores, with a theoretical range of 10 to 50. GDM was diagnosed by the 75-g 2-h oral glucose tolerance test at 24–28 wks. Cubic-restricted spline function and logistic regression analyses were used to examine the association between the PDI during pregnancy and GDM. Results: GDM was reported by 8.1% of the 2099 pregnancies. The PDI score ranged from 17 to 43 (theoretical range: 10–50), the mean (SD) was 30.2 (4.4). After adjusting for maternal age, ethnicity, education, income, parity, gravidity, family history of diabetes, total energy intake per day, and other pre-pregnancy information such as body mass index (BMI), smoking status, drinking status, exercise, and sleep quality, a linear association between the PDI and GDM risk was demonstrated by the restricted cubic splines ( P for overall association = 0.024, P for nonlinearity = 0.370). Compared to the lowest quartile 1 of PDI, ORs (95% CI ) were 0.91 (0.59, 1.42) for quartile 2, 0.91 (0.58, 1.41) for quartile 3, and 0.52 (0.30, 0.89) for quartiles 4 ( P for trend = 0.040) in the adjusted model. Conclusions: Our study suggests that higher PDI is associated with a substantially lower risk of developing GDM, which indicates that adopt plant-based diets during pregnancy could be an easy avenue to reduce GDM risk. Funding Sources: Funding was received from the National Program on Basic Research Project of China (NO.2013FY114200) and the Fundamental Research Funds for the Central Universities (HUST2016YXZD040) for Nianhong Yang.